Building your own robots - McComb, Gordon (John Wiley and Sons, 2016)
There's no better way for kids to learn about the world around them than to test how things work. Building Your Own Robots presents fun robotics projects that children aged 7 – 11 can complete with common household items and old toys. The projects introduce core robotics concepts while keeping tasks simple and easy to follow, and the vivid, full-color graphics keep your kid's eyes on the page as they work through the projects.